Analisis Buku Siswa Matematika Kelas IV Sekolah Dasar Kurikulum 2013 Revisi 2018 Ditinjau dari Penerapan Pendekatan Etnomatematika - Sulistianingsih, Isra; Irawati, Riana; Maulana, Maulana (Jurnal Pena Ilmiah, 2021)
This research is conducted on the basis that ethnomathematics is a bridge between mathematics and culture, and the ethnomathematics approach is one way to bridge the gap between that. Ethnomathematics has begun to be integrated in the curriculum 2013 and has an important to improving the quality of mathematics learning. This research is a qualitative by using descriptive methods and document analysis design. The research object is the mathematics student book and 18 grade IV students as research subjects. The research instruments used assessment document sheets, teacher and student activities observation sheets, student response questionnaires, and teacher response interview sheets. The results of this research indicate that mathematics student book curriculum 2013 revised 2018 for class IV can be implemented with an ethnomathematics approach, and the application of the ethnomathematics approach is one of solution to innovate and creative creating to a meaningful form of mathematics learning.